2021
DOI: 10.21608/ejchem.2021.56260.3207
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of CuO nanoparticles stabilized by quercetin and its application for anti-breast cancer activity

Abstract: The main idea in this research used quercetin (QT) as a stabilizing agent to prepare CuO nanoparticle (NPs). QT is a pigment which exists from plants, fruits, and in some medicines. It contains numerous hydroxyl groups, works as a complexing agent and a self-assembly agent. The prepared CuO-NPs were characterized by Fourier transformed infrared (FT-IR), X-ray diffraction (XRD), scanning and transmission electron microscopy (SEM and TEM), and energy-dispersive X-ray analysis (EDX). The structure investigation c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
2
2
0
Order By: Relevance
“…The results of S. epidermidis showed that the inhibition zone diameter values were 16.4 mm at a concentration of 100 μg/mL, 15.2 mm at 75 μg/mL, and 13.5 mm at 50 μg/mL, while at the concentration of 25 μg/mL, the diameter recorded was 11.6 mm. The results of the present study agree with those of Alishah et al, where CuO NPs were found to have an inhibitory effect on S. epidermidis [9]. As for P. aeruginosa, the diameter of the zone of inhibition showed values of 17 mm at 100 μg/mL, 16.4mm at 75 μg/mL, 15.2 mm at 50 μg/mL, and 13.26 mm at 25 μg/mL.…”
Section: Antibacterial Activity Of Cuo Npssupporting
confidence: 92%
“…The results of S. epidermidis showed that the inhibition zone diameter values were 16.4 mm at a concentration of 100 μg/mL, 15.2 mm at 75 μg/mL, and 13.5 mm at 50 μg/mL, while at the concentration of 25 μg/mL, the diameter recorded was 11.6 mm. The results of the present study agree with those of Alishah et al, where CuO NPs were found to have an inhibitory effect on S. epidermidis [9]. As for P. aeruginosa, the diameter of the zone of inhibition showed values of 17 mm at 100 μg/mL, 16.4mm at 75 μg/mL, 15.2 mm at 50 μg/mL, and 13.26 mm at 25 μg/mL.…”
Section: Antibacterial Activity Of Cuo Npssupporting
confidence: 92%
“…The peaks positions and relative intensities of the diffraction peaks of (32.5⁰, 35.5⁰, and 38.9⁰) correspond to the lattice plane of (110), ( 111) and (002) respectively reflections, in agreement with JCPDS data for CuO (JCPDS: card no. 48-1548) [27][28][29]. Therefore, the result here confirmed the evaporated films are CuO.…”
Section: Characterization Of the Cuo Nanorodssupporting
confidence: 79%
“…Currently, several reports are focused on metal oxides, including aluminium oxide (Al 2 O 3 ), copper oxide (CuO), nickel oxide (NiO), etc. Moreover, more attention has been focused on the perspective of copper oxide in various aspects such as antibacterial agents [12], catalysis [13], food packaging [14], sensors [15] and medicine [16]. Recently, there has been a growing awareness of the development of aluminium oxide nanoparticles (Al 2 O 3 NPs) which have a high specific surface area with extraordinary optical, catalytic, thermodynamic stability properties for progressive engineering and industrial applications [17][18][19].…”
Section: Introductionmentioning
confidence: 99%